Reality Show, Sebuah Tren Baru Acara Pertelevisian - Ranang Agung S (Institut Seni Indonesia Surakarta, 2004)
Reality shows recently being a new trend on our national television which actually was a genre development from reality shows that was born in the beginning of 20th century on overseas. And most of Indonesian people societies and telecommunication techno(ogy.Pro and con to the reality shows should be focused the specific matters. And of course, it is not proper if we only would judge to all of them, since there are so many kinds of reality shows. Reality shows is a really good business modelf or the TV itself. It is also very appropriate to the characteristic of the TV media itself and it is also giving chance to the viewers to participate actively when they wacthing the live shows play on the TV.In the articles will be discussed about the definition of reality shows, the progress of local product of the reality shows, AFI dan Indonesian Idol, the viewers emotion, education value and the business point of view of the reality shows.Keyword: reality, show, television